2020
DOI: 10.1016/j.microrel.2020.113697
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of vibration on power electronic module structure and application of model order reduction

Abstract: Modelling and analysis of vibration of an IGBT power electronic module (PEM) structure were undertaken. PEM structure considered in this study was without molding compound and wirebonds. The most critical resonant frequency was identified by modal analysis. At the critical frequency of 1345Hz, for the vertical displacement of the base excitation, subsequent stress distribution on the PEM structure was analysed. Concurrent vibration and thermo-mechanical fatigue loads on the reliability of PEM structure solder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Thus, learning media are needed to accommodate the essential empowerment of thinking skills. In addition, the way to improve critical thinking skills is to develop teaching materials such as electronic e-modules (e-modules) (Pierce & de Man, 2019; Rajaguru et al, 2020;Wahidah et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, learning media are needed to accommodate the essential empowerment of thinking skills. In addition, the way to improve critical thinking skills is to develop teaching materials such as electronic e-modules (e-modules) (Pierce & de Man, 2019; Rajaguru et al, 2020;Wahidah et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the way to improve critical thinking skills is to develop teaching materials such as electronic e-modules (e-modules) (Pierce & de Man, 2019;Rajaguru et al, 2020;Wahidah et al, 2019). E-modules have strategic value in practicing critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…JiaJia Guan et al further considered the response of power devices to random vibration under thermal loads and found that thermal stress can affect the structural stiffness and thus stress under vibration [ 3 ]. Pushpa Rajaguru assessed solder layer reliability under thermal and vibrational loads and concluded that vibration-induced damage surpasses damage from thermomechanical fatigue at critical resonant frequencies [ 4 ]. Xinlan Hu et al used finite element simulation to study the combined effects of electrical–thermal loads and random vibrations on solder joint reliability [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…By establishing the finite element model of electronic packaging devices, Qin [ 17 ] carried out a series of vibration fatigue experiments on the solder joints of electronic packaging devices, and modified the Steinberg model according to the research results. Rajaguru modeled and analyzed the vibration of the power electronic module (PEM) structure, taking the random vibration of the vehicle as the excitation, and drew the conclusion that the vibration has an obvious influence on the fatigue life of the electronic structure [ 18 ]. Similarly, with the road load as the incentive, the research results of Wang show that even the piezoelectric energy collector specifically used to collect road vibration energy will experience the problem of performance degradation under the continuous action of traffic load [ 19 ].…”
Section: Introductionmentioning
confidence: 99%